CARLEMAND FUNCTION FOR BIHARMONIC FUNCTIONS IN SOME UNLIMITED SET OF 2-DIMENSIONAL SPACE. - Зебинисо Рахимовна Ашурова; Умидахон Юнусалиевна Жураева; Фируза Уткуржоновна Маллаева, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
In this article we consider Carlеman’s functions, to find integral representation for the polygarmonious functions(Δ2u(y) = 0) defined in unbounded domain of Euclidean space obtaining an integral representation, with its help, a theorem of the Fragmen-Lindelef type is obtained